Teachers Perception of the effects and use of learning aids in teaching: a case study of Winneba basic and secondary schools. - Adeyanju, Lade (2014)
Learning and teaching is the concern of the trained teacher. But learning is a complex process. It can however be defined as a change in disposition; a relatively permanent change in behaviour overtime and this is brought about by experience. Learning can occur as a result of newly acquired skill, knowledge, perception, facts, principles, new information at hand etc. Learning can be reinforced with learning aids of different variety because they stimulate, motivate as well as arrest learner's attention for a while during the instructional process.